"Negotiating, Navigating, and Networking": Three Strategies Used by Nursing Leaders to Shape the Adoption and Incorporation of Simulation into Nursing Curricula—A Grounded Theory Study. (8th April 2014) - Taplay, Karyn; Jack, Susan M.; Baxter, Pamela; Eva, Kevin; Martin, Lynn
Abstract : Background . Implementing simulation requires a substantial commitment of human and financial resources. Despite this, little is known about the strategies used by academic nursing leaders to facilitate the implementation of a simulation program in nursing curricula. Methods . A constructivist grounded theory study was conducted within 13 nursing programs in Ontario, Canada. Perspectives of key stakeholders( n = 27 ) including nursing administrators( n = 6 ), simulation leaders( n = 9 ), and nursing faculty( n = 12 ) were analyzed using the constant comparison method. Results . Nursing leaders, specifically nursing administrators and simulation leaders who successfully led the adoption and incorporation of simulation into nursing curricula, worked together and utilized negotiating, navigating, and networking strategies that impacted the adoption and incorporation of simulation into nursing curricula. Conclusions . Strategies that were found to be useful when planning and executing the adoption and incorporation of an innovation, specifically simulation, into nursing curricula provide practical approaches that may be helpful to nurse leaders when embarking upon an organizational change.